Analisis Insektisida Organoklorin Pada Bulu Walet Sarang Putih (Collocalia fuciphaga Thunberg) - Oktaf Laudensius; Pramana Yuda; Kianto Atmodjo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
The objectives of this study are to find out the kind and quantitative  of organochlorine insecticide  in  swallow (Collocalia fuciphaga Thunderberg) feathers.  The samples were plumae of wing and tail feathers from the birds were catched in Siluk, Gunungkidul and  Sedayu, Bantul on August and September 2002 The organochlorine insecticide compound were analysed by  gas chromatography-electronic catcher detector. The analysis result found out  the organochlorine insecticide in swallow feathers, were heptachlor (0-5855 ppm) and pp-DDD (0-0929 ppm).